2002
DOI: 10.1038/sj.onc.1205446
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant promoter methylation and silencing of the RASSF1A gene in pediatric tumors and cell lines

Abstract: Aberrant promoter methylation of tumor suppressor genes has not been fully investigated in pediatric tumors. Therefore, we examined the methylation status of nine genes (p16 INK4A , MGMT, GSTP1, RASSF1A, APC, DAPK, RARb, CDH1 and CDH13) in 175 primary pediatric tumors and 23 tumor cell lines using methylation-speci®c PCR. We studied the major forms of pediatric tumors ± Wilms' tumor, neuroblastoma, hepatoblastoma, medulloblastoma, rhabdomyosarcoma, osteosarcoma, Ewing's sarcoma, retinoblastoma and acute leukem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
152
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(175 citation statements)
references
References 23 publications
18
152
5
Order By: Relevance
“…The frequency of SLIT2 methylation in NB was less than that for RASSF1A and CASP8, but is still a significant finding as other candidate TSGs that demonstrate frequent promoter methylation in some cancers (e.g. p16INK4A, MGMT, RARâ, DAPK, APC, GSTP1, CDH1 and CDH13) are rarely methylated in NB (Harada et al, 2002a).…”
Section: Discussionmentioning
confidence: 87%
“…The frequency of SLIT2 methylation in NB was less than that for RASSF1A and CASP8, but is still a significant finding as other candidate TSGs that demonstrate frequent promoter methylation in some cancers (e.g. p16INK4A, MGMT, RARâ, DAPK, APC, GSTP1, CDH1 and CDH13) are rarely methylated in NB (Harada et al, 2002a).…”
Section: Discussionmentioning
confidence: 87%
“…31 Previous studies, including ours, have repeatedly shown that promoter hypermethylation of RASSF1A correlated with loss of expression in various cancers, and treatment with a demethylating agent reactivated RASSF1A gene expression in various cancer cell lines, including a hepatoblastoma cell line HepG2. 9,34,36,37 RASSF1A inhibits tumor formation by apoptosis, and regulates microtubule dynamics and mitotic arrest via multiple effectors. By dysregulation of the Ras signaling pathway, RASSF1A methylation is correlated with poor differentiation and vascular invasion of cancer cells, and an unfavorable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…6 Previous studies have shown that epigenetic TSG inactivation plays a role in medulloblastoma development. [7][8][9][10][11][12][13][14][15] To date, 3 genes have demonstrated strong and consistent evidence of epigenetic inactivation by promoter methylation in a significant proportion of medulloblastomas: RASSF1A, CASP8 and HIC-1. [8][9][10][11][12]14,15 Together these data suggest that further epigenetic events are involved in medulloblastoma; however, the role of hypermethylation events in stPNET pathogenesis has not been widely investigated.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] To date, 3 genes have demonstrated strong and consistent evidence of epigenetic inactivation by promoter methylation in a significant proportion of medulloblastomas: RASSF1A, CASP8 and HIC-1. [8][9][10][11][12]14,15 Together these data suggest that further epigenetic events are involved in medulloblastoma; however, the role of hypermethylation events in stPNET pathogenesis has not been widely investigated.MCJ (also DNAJD1) is a recently discovered gene on chromosome 13q14.1 which is inactivated in over 50% of ovarian cancer cell lines and primary tumours by epigenetic transcriptional silencing (through hypermethylation of a CpG island which lies within the 5 0 transcribed region of the MCJ gene) and genetic deletion. 16,17 MCJ contains a highly conserved 70-amino acid DNAJ domain (or J domain), first described in the Escherichia coli Hsp DNAJ.…”
mentioning
confidence: 99%